2018
DOI: 10.1097/ftd.0000000000000463
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Antifactor Xa and Activated Partial Thromboplastin Time Monitoring for Heparin Dosing in Vascular Surgery Patients: A Single-Center Retrospective Study

Abstract: The use of anti-Xa levels for heparin titration showed higher rates of major bleeding complications in vascular surgery patients compared with aPTT monitoring, but no significant difference was identified in this study. Vascular surgery patients with relatively high aPTT to anti-Xa values may have an increased risk of bleeding complications when heparin is titrated based on anti-Xa levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
0
7
1
Order By: Relevance
“…This result is consistent with a previous study that showed no difference in major or minor bleeding rates or PRBC transfusions in vascular surgery patients. 12 Whereas Belk et al 13 found that patients diagnosed with stroke, ACS, or VTE across approximately 400 hospitals across the United States required significantly fewer transfusions after transitioning to using anti-Xa monitoring, our study did not find a similar decrease, likely because of the smaller sample size. However, our findings appear to reinforce that the transition to an anti-Xa based protocol seems to be safe in the elderly veteran population, with no increase in bleeding risk.…”
Section: Discussioncontrasting
confidence: 87%
“…This result is consistent with a previous study that showed no difference in major or minor bleeding rates or PRBC transfusions in vascular surgery patients. 12 Whereas Belk et al 13 found that patients diagnosed with stroke, ACS, or VTE across approximately 400 hospitals across the United States required significantly fewer transfusions after transitioning to using anti-Xa monitoring, our study did not find a similar decrease, likely because of the smaller sample size. However, our findings appear to reinforce that the transition to an anti-Xa based protocol seems to be safe in the elderly veteran population, with no increase in bleeding risk.…”
Section: Discussioncontrasting
confidence: 87%
“…24 Anti-FXa levels is preferred to monitor heparin activity to aPTT because anti-FXa assay directly reflects functional activity of heparin and less affected by patient and analytic variables. 27 Moreover, elevated factor VIII and fibrinogen levels and increased plasma heparinbinding proteins during pregnancy can also cause a resistance to aPTT test, which makes it a poor sensitive test to monitor the efficacy and safety of heparin treatment as compared with heparin anti-FXa levels which is not affected. 27,28 The blunted aPTT response to therapeutic heparin during pregnancy can result in over-anticoagulation and increased the risk of bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…27 Moreover, elevated factor VIII and fibrinogen levels and increased plasma heparinbinding proteins during pregnancy can also cause a resistance to aPTT test, which makes it a poor sensitive test to monitor the efficacy and safety of heparin treatment as compared with heparin anti-FXa levels which is not affected. 27,28 The blunted aPTT response to therapeutic heparin during pregnancy can result in over-anticoagulation and increased the risk of bleeding. However, true heparin resistance can occur in patients with antithrombin deficiency, increased clearance, or increased heparin-binding proteins (often considered acute phase reactant).…”
Section: Discussionmentioning
confidence: 99%
“…Anticoagulant dosing of obese patients with PE remains to be an area that has not been well studied [72]. The bulk of the data comes from pharmacokinetic/ pharmacodynamic (PK/PD) studies and subgroup analyses of premarketing trials comparing obese patients to patients with normal body weight [52][53][54]72]. Furthermore, warfarin appears to have the most robust data available in this population.…”
Section: Special Population 91 Obesitymentioning
confidence: 99%
“…These studies enrolled some patients with BMIs >35 kg/m 2 and found clinical benefits comparable across all weight groups [58]. The authors of this analysis also concluded that standard doses should be sufficient to treat obese patients; however, a review questioned whether the data were robust enough to draw that conclusion [52,58].…”
Section: Special Population 91 Obesitymentioning
confidence: 99%